Information System Construction and Application of the Standardized Test Center Based on Internet - Lu Zhang; Ping Li; Shiping Jin; Chun Jing (Dianxin kexue)
Based on the construction of internet information system，the basic specification of the standardized test center was studied and a set of comprehensive business requirements including monitoring，communication，audio，video and education examination management technology was proposed.The standardized test center design principles were analyzed and developed，according to the designed business function module，the composition，the system overall structure and the application system.The technology implementation scheme including on-line inspection system，video conference system，cheating prevention and control system，identity authentication system and display system were given.Finally，the integration and connection of internet and the educational research network in China were analyzed，and the other entry way when the condition was unavailable.